2019
DOI: 10.1590/0102-672020190001e1438
|View full text |Cite
|
Sign up to set email alerts
|

Does Male Gender Increase the Risk of Laparoscopic Cholecystectomy?

Abstract: Background: Laparoscopic cholecystectomy is the preferable treatment for chronic or acute cholecystitis. Some factors may increase the rate of laparoscopic conversion to open cholecystectomy and perioperative complications. The role of gender as a risk factor for laparoscopic cholecystectomy is controversial. Aim: To evaluate the role of the gender on the operative findings and outcome of laparoscopic cholecystectomy. Method: All patients who underwent laparoscopic cholecystectomy for chronic or acute cholec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
2
19
1
6
Order By: Relevance
“…The researcher only points to a longer operation time in men (72.48 ± 28.50) than in women (65.46 ± 24.83, p < 0.001). The presented results may be a consequence of the unequal distribution of the studied groups of women and men (32.8% vs. 67.2%) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The researcher only points to a longer operation time in men (72.48 ± 28.50) than in women (65.46 ± 24.83, p < 0.001). The presented results may be a consequence of the unequal distribution of the studied groups of women and men (32.8% vs. 67.2%) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,15,22 This study reported a significant difference between male and female groups in terms of prior abdominal surgeries (p=0.006) and a similar trend was observed in a study by Kumar et al 22 In contrast, studies by and Genc et al and Coelho al. 9,29 did not show any significant difference in between male and female groups. Since, our research included cases with history of only lower abdominal surgeries; this could not negatively influence the outcome of surgery.…”
Section: Discussionmentioning
confidence: 65%
“…The results of our study revealed that no significant difference was there in duration of surgery between male and female groups (p=0.85). On the contrary, studies by Bazoua et al, Alqahtani et al, Akcakaya et al, Ambe et al, Kanakala et al, Coelho et al 15,17,18,29 The average operative time was longer in males than females and difference was significant statistically. In this study, postoperative hospital stay was similar for both men and women groups and this finding can be correlated to studies by Bazoua et al, Kumar et al and Coelho et al 15,22,29 In contrast, some studies reported a longer duration of post-operative stay in male patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations